Proses PEMBUATAN BUBUK DAUN KELOR (Moringa oleifera) SEBAGAI TAMBAHAN MAKANAN FUNGSIONAL BERDASARKAN SUHU DAN LAMA PENGERINGAN YANG BERBEDA - Nurul Muchlisah Zainuddin; Sri Hajriani (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2021)
Moringa (Moringa oleifera) has been known for centuries as a multipurpose plant, nutrient dense and efficacious as medicine. However, the manufacture of Moringa into flour or powder and its development into additional functional food has not been done much. One effort that can be done is to make flour from Moringa leaves as an addition to nutrient-rich functional foods. The main content of this Moringa leaf turns out to be higher if the Moringa leaves are processed first into a dry or flour form. This study aims to determine the best drying temperature and drying time used in the process of making Moringa leaf powder based on chemical analysis, vitamin C and moisture content and to determine the organoleptic properties of Moringa leaf powder based on different temperatures and drying times. The research method used is to determine the best drying temperature and drying time using drying temperatures (35 oC, 50 oC, and 65 oC). Drying time (5 hours, 6 hours and 7 hours). The best drying temperature and time will be determined by testing the chemical analysis of Moringa leaf flour, vitamin C and moisture content tests and organoleptic tests, (hedonic method). The results of the research on the best Moringa leaf powder formulation based on the analysis of vitamin C and moisture content were the treatment with a drying temperature of 35 oC and a drying time of 5 hours. The most preferred organoleptic properties in the form of texture, taste and aroma are the treatment at a drying temperature of 65 oC and a drying time of 7 hours, while the most preferred color is at a treatment of 35 oC and a drying time of 5 hours.